APPROACHES TO TEACHING VOWEL SOUNDS OF THE JAPANESE LANGUAGE TO NON-NATIVE (UZBEK) LEARNERS - Fatkulina Luiza (Journals Park Publishing, 2024)
Teaching non-native speakers the phonology of Japanese can be seen as a dual challenge and a unique requirement, necessitating additional investigations. In this article we would like to address the issues on teaching Japanese vowels to the learners of Uzbekistan. The problem will be detected by conducting practical experiment including 30 students. The reading text is appointed to investigate the pronunciation errors made by the students. The solutions for strengthening teaching Japanese phonology will be proposed.
Keywords: phonology, vowels, pronunciation, sound, Japanese.